2014
DOI: 10.3109/01443615.2014.948818
|View full text |Cite
|
Sign up to set email alerts
|

Levels of neopterin and C-reactive protein in pregnant women with fetal growth restriction

Abstract: The aim of this study was to evaluate whether pregnant women with fetal growth restriction (FGR) have higher plasma neopterin and C-reactive protein (CRP) concentrations compared with those with uncomplicated pregnancy. A total of 34 pregnant women with FGR and 62 patients with uncomplicated pregnancy were included. Neopterin and CRP levels were measured at the time of diagnosis. The primary outcome of this study was to compare the neopterin and CRP levels in pregnant women with FGR and those with uncomplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Erkenekli et al demonstrated that pregnant women with fetal growth retardation had significantly elevated neopterin levels . Furthermore, plasma neopterin levels were higher in pre‐eclamptic women compared with women with uncomplicated pregnancies.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Erkenekli et al demonstrated that pregnant women with fetal growth retardation had significantly elevated neopterin levels . Furthermore, plasma neopterin levels were higher in pre‐eclamptic women compared with women with uncomplicated pregnancies.…”
Section: Discussioncontrasting
confidence: 46%
“…8 Erkenekli et al demonstrated that pregnant women with fetal growth retardation had significantly elevated neopterin levels. 23 Furthermore, plasma neopterin levels were higher in pre-eclamptic women compared with women with uncomplicated pregnancies. CRP has also been correlated with neopterin in women with transient hypertension of pregnancy and women with preeclampsia.…”
Section: Discussionmentioning
confidence: 97%
“…Serum CRP may predict preeclampsia [35], and may be a risk marker for preterm birth, perhaps by reflecting intrauterine infection [36]. But as a predictor of FGR, only inconsistent associations have been found [37, 38]. A recent prospective study documented that high maternal CRP predicted lower birth weight, but did not adjust for gestational age at birth [39].…”
Section: Discussionmentioning
confidence: 99%
“…SGA birth was not associated with raised CRP concentrations, and raised values were actually lower at ANC1 for this outcome. Previous studies in non-malaria endemic areas have reported a positive association with fetal growth restriction but only when CRP levels were very high (> 25 mg/l) [42], a weak positive association in late pregnancy [43], or no association [44]. In Papua New Guinea, CRP at enrolment and at delivery in women receiving sulphadoxine-pyrimethamine plus chloroquine (compared to sulphadoxine-pyrimethamine plus azithromycin), was positively associated with PTB, but not SGA [45].…”
Section: Discussionmentioning
confidence: 99%